Reduction the Costs of Investigating in Financial Industry Based on Activity-Based Costing and Supply Chain - Asaad Sasaa Agrab; Mlath Abd Al- Gbar Abas; Hayder Mmatloob Koshan (International Journal of Supply Chain Management, 2019)
Abstract- Responding to the needs of shareholders and investors, earning profit and income and covering current expenses are the hugest goals of each economic unit. Banks and financial institutions also have these rules. Perhaps the most important thing for them is calculating and understanding the cost of money. Because calculating cost reductions and analyzing it can be used to estimate and execute the amount and cost of paying the facility, and also the profits of the deposits in each supply chain system. However, it should be noted that the issue of reducing costs, including goods made, sold goods, services provided or time consumed, is one of the most complex accounting issues. Besides, it is certainly more costly to calculate the cost of services than the calculation of reducing goods costs. Therefore, what is said is a general overview of the very complex process of calculating the expense of money and reducing costs in financial institutions based on the supply chain. In this research, we will consider the reduced costs of investigating in the financial industry based on activity-based costing and supply chain. Keywords: Bank, Investment, Activity-Based Costing (ABC), supply chain, costs.